2021
DOI: 10.1007/s40257-020-00583-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dupilumab on Laboratory Parameters in Adolescents with Atopic Dermatitis: Results from a Randomized, Placebo-Controlled, Phase 3 Clinical Trial

Abstract: Background Laboratory testing is typically required for patients with atopic dermatitis (AD) treated with systemic immunosuppressants. A previous analysis of laboratory outcomes in randomized, double-blinded, placebo-controlled clinical trials of dupilumab in adults with moderate-to-severe AD found no clinically important changes in hematologic, serum chemistry, and urinalysis parameters, supporting the use of dupilumab without routine laboratory monitoring. Objective T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 33 publications
9
27
3
3
Order By: Relevance
“…Dupilumab + TCS-associated decreases in platelet counts and LDH were similar to those reported in adolescents and may represent improvements in AD-associated inflammation. These findings are consistent with outcomes previously reported in adolescents and adults with moderateto-severe AD [16,17], support the pivotal efficacy and safety data previously reported for this clinical trial [15], and echo the observed trends in minor laboratory differences seen in adolescents and adults treated with this biologic agent [16,17]. Together with the results of previous studies in adults and adolescents, these data provide support that dupilumab does not require routine laboratory monitoring before initiation or during treatment in children aged 6-11 years with severe AD.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Dupilumab + TCS-associated decreases in platelet counts and LDH were similar to those reported in adolescents and may represent improvements in AD-associated inflammation. These findings are consistent with outcomes previously reported in adolescents and adults with moderateto-severe AD [16,17], support the pivotal efficacy and safety data previously reported for this clinical trial [15], and echo the observed trends in minor laboratory differences seen in adolescents and adults treated with this biologic agent [16,17]. Together with the results of previous studies in adults and adolescents, these data provide support that dupilumab does not require routine laboratory monitoring before initiation or during treatment in children aged 6-11 years with severe AD.…”
Section: Discussionsupporting
confidence: 92%
“…Mean platelet counts decreased, but remained within normal range, in both dupilumab + TCS groups, most likely reflecting diminished acute phase reactant activity linked to AD severity [ 21 , 22 ]. Similar trends were seen in previous studies in adults [ 16 ] and adolescents [ 17 ], also without adverse clinical implications. AD is a chronic inflammatory condition with a dynamic course characterized by recurrent acute exacerbations, which can cause oscillating levels of acute phase reactants along with chronic elevations of systemic markers of inflammation [ 21 24 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations